2014
DOI: 10.1111/dar.12128
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alcohol policies and public opinions in Finland 2003–2013

Abstract: It seems that an increased level of awareness of alcohol-related issues among the general public created a more restrictive opinion climate on alcohol policy issues after the big alcohol excise duty decrease in 2004. The reverse seems to happen but in a lesser degree when alcohol excise duties has been increased after the year 2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 7 publications
(17 reference statements)
2
24
0
Order By: Relevance
“…Some age and income differences were also noted. These findings are consistent with previous studies in developed countries that found higher levels of support for certain alcohol policies among women [9,11,15,16,18,19], older persons [9,15,18,19] and less heavy drinkers [9,11,15,16,18]. Like other studies, this research did not find that support for alcohol policies varied by income [9].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Some age and income differences were also noted. These findings are consistent with previous studies in developed countries that found higher levels of support for certain alcohol policies among women [9,11,15,16,18,19], older persons [9,15,18,19] and less heavy drinkers [9,11,15,16,18]. Like other studies, this research did not find that support for alcohol policies varied by income [9].…”
Section: Discussionsupporting
confidence: 92%
“…Across a variety of developed countries, support for more restrictive alcohol policies tends to be highest among women [9,11,15,16,18,19], older people [9,15,18,19] and light or non-drinkers [9,11,15,16,18]. Mixed findings have been observed regarding the effect of education and income [9,15,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esa Österberg and colleagues [3] examine alcohol policies and public opinion in Finland over a recent decade (2003–2013) during a time of dramatic changes in alcohol policies. They conclude that with increasing alcohol consumption, there was a shift towards greater support for more restrictive alcohol policies.…”
mentioning
confidence: 99%
“…36 In the US, no states have established control systems since the immediate post-Prohibition period; thus, expanding such systems might meet opposition from those who would like to eliminate them, including the alcohol industry. 16 In other countries (for example, Finland and the Scandinavian countries), government retail monopolies may be better accepted 37 and expansion into tobacco products better received. The addition of marijuana sales to government stores and framing expansions of the system as a means to rationalizing substance regulation could also increase public acceptance.…”
Section: Challenges and Potential Concernsmentioning
confidence: 99%